Smart bridge for memory core - D'Abreu Manuel Antonio; Skala Stephen; Nair Radhakrishnan; Pantelakis Dimitris; Pancholi Deepak (2016)
An apparatus includes a first semiconductor device including a NAND flash memory core. The apparatus also includes a second semiconductor device including periphery circuitry associated with the NAND flash memory core.